UK military veteran-friendly GP practices. Issue 1 (22nd February 2021) - Simpson, Robin G; Leach, J
Abstract : About 5% of the UK population are military veterans and have specific medical needs sometimes different from the general population. Veterans may be reluctant to seek help or talk about their problems, which means they do not always access care, support and treatments that are available. Others may face difficulty getting the right help. Veterans may think 'civilians' do not understand military culture or know about options for help and services that are available. Experience has shown that general practitioners (GPs) would like more help and support when looking after veterans. The Royal College of General Practitioners has developed the 'Veteran Friendly GP Practice Accreditation Programme', which involves a simple online process of accreditation where practices are required to meet the specified criteria and provide evidence that they are supportive of veterans' healthcare. The aim is to improve healthcare provided to veterans and their families by GPs working in primary healthcare.